Space vector PWM method for Ultra sparse atrix converter using FPQA xc3s500e - Tran, Vũ; Nguyen, Văn Nhờ (Journal of Technical Education Science, 2010)
The Ultra Sparse Matrix converter (USMC) circuit, which simply consists of nine single switches, shows a great advantage to a much more burdensome conventional Matrix converter, which involves a double number of switches. Being due to this least number of switches, USMC is the most compact design. Despite its restricted requirement of unidirectional power flow applications, USMC has the same high quality output waveform of conventional Matrix converter. In this paper, a whole control algorithm of USMC was entirely designed on Xilinx XC3S500E Spartan-3E FPGA. The algorithm’s efficiency is verified through simulation and experiment work for switching strategy of USMC. Experimental results of switching gate signals are shown and compared to theoretical switching sequence. Experimental input and output waveforms are also analyzed.